Quality of life after reconstruction of traumatic orbital floor defects using titanium mesh and medpore: A randomised controlled trial - Sneha Gupta; Divya Mehrotra; Praveen Kumar Singh; Vignesh U; Sujay Bhave; Ravi Katrolia (Elsevier, 2021)
Aim and objectives: The aim of this study was to analyse the outcomes of orbital floor reconstruction with two types of orbital implants and assess patients' quality of life. Material and methods: 39 sequential patients with clinical and radiological evidence of orbital floor fracture, presenting diplopia, enophthalmos, paraesthesia or a post traumatic residual orbital deformity were included in this study and randomised for orbital floor reconstruction using porous polyethylene sheet (Biopore™) or preshaped titanium mesh on a 3D model. Their pre and postoperative quality of life were compared. Success rate was assessed and scored with a minimum of zero (none) and a maximum of ten (excellent) for improvement in the signs of diplopia, enophthalmos, hypoglobus, paraesthesia and aesthetics. Results: Both QOL scores and Success score was greater in cases which reconstruction of orbital floor was performed with preshaped titanium mesh as compared to those with Biopore™. Conclusion: Preshaped titanium mesh shows better results than reconstruction with Biopore™. However a large sample size and a long term follow up is needed for generating the best evidence. Quality of life extensively improves after orbital floor reconstruction motivating the patients desire to live.